Actinin-4 splice variant - a complementary diagnostic and prognostic marker of pancreatic neuroendocrine neoplasms - Xu, Xiaojun; Honda, Kazufumi; Miura, Nami; Le Blanc, Solange; Bergmann, Frank; Gaida, Matthias; Volkmar, Michael; Schimmack, Simon; Hackert, Thilo; Strobel, Oliver; Felix, Klaus M. (Journal of cancer, 2020)
Introduction: For pathological diagnosis of pancreatic neuroendocrine neoplasms (pNENs) the routinely used immunohistochemical markers are chromogranin A (CgA) and synaptophysin (Syn). Their ability as prognostic markers is not well established. A splice variant of actinin-4 (Actn-4sv) was recently found to be an excellent biomarker of neuroendocrine neoplasms of the lung. We aimed to investigate the expression of Actn-4sv in pNENs and evaluate its quality as a biomarker of pNENs. Methods: Paraffin-embedded and frozen tissues specimens from 122 pNENs were analyzed. Western blots were performed to prove and compare the relative amount of Actn-4sv expression in pNENs tissue homogenates. For comparison pancreatic ductal adenocarcinoma (PDAC) and normal pancreatic tissues were analyzed in parallel. Immunohistochemistry (IHC) of paraffin sections of pNENs for Actn-4sv were performed and compared to the classic neuroendocrine markers CgA and Syn. Correlations were calculated between the staining intensity and distribution of Actn-4sv and staging, grading and afflicted lymph nodes respectively. Results: Actn-4sv was expressed in 88.5% (108/122) of pNENs, but not in normal pancreatic tissues (0/14) or PDAC (0/14). Compared to CgA and Syn, Actn-4sv was not detectable in islet cells of the normal pancreas. Staining intensity of Actn-4sv on pNENs negatively correlated to the histological grading (Spearman r=-0.4990, p<0.0001) and staging (r = -0.2581, p = 0.0041) but no correlation to afflicted lymph nodes was found. A significantly better overall survival was observed for pNEN patients with higher expression of Actn-4sv (hazard ratio 2.7; log-rank test p= 0.0349). Conclusions: The expression of Actn-4sv may be an important prognostic factor for patients with pNENs. Its expression correlates with the grading and staging of the tumors.
Gesehen am 14.04.2020